Uno strumento per l'orientamento differenziale in professioni di confine: educatore, insegnante, assistente sociale, psicologo - Paola Ricchiardi; Emanuela Torre (LED Edizioni Universitarie, 2021)
The choice of the university course to attend and therefore indirectly the professions connected to it, constitutes a complex operation for a student who finishes secondary school (Vulperhorst, 2020). This choice becomes more difficult if we are talking about courses of study that train border professions, as in the case of university courses in the socio-psycho- pedagogical field, assimilated, in the common feeling, to the point of confusing the borders. The accompaniment of secondary school students oriented towards these professions requires adequate tools for exploring the same, tools that allow them to analyze the congruence between their interests, skills, personal attitudes and the chosen professional profiles. For this purpose we have built and validated a tool for socio-psycho-pedagogical professions, to be used in differential orientation paths for students who need assistance in the discrimination of the paths that lead to the training of educators, teachers, psychologists and social workers. We will start the contribution with an analysis of the dysfunctional choice mechanisms that most typically lead to inappropriate choices in the study paths indicated, to then arrive at illustrating the original tool.